LONG-COVID IMPACT ON THE REPRODUCTIVE HEALTH OF WOMEN WITH FERTILITY - Golovchak, I.S.; Boichuk, O.H.; Kupchak, I.M. (World of Medicine and Biology, 2024)
Reproductive health is a fundamental human right crucial for the health, well-being, and quality of life of individuals, families, communities, society, and the state. To determine the possible impact of COVID-19 on women’s reproductive health, we included 80 patients who came to the clinic of reproductive technologies for infertility treatment in a comprehensive examination and were divided into 2 groups. The main group consisted of 60 women after COVID-19 (10 patients with only a male infertility factor were excluded, and one patient refused to participate in the study); the comparison group consisted of 20 patients without a history of COVID-19. The study was carried out using the principles of the Declaration of Helsinki. The research protocol was approved by the institution’s Local Ethics Committee, mentioned in the work. Informed consent was obtained from the women for the study. Among patients with infertility, a high frequency of long COVID has been established, the consequences of which are various disorders of somatic and reproductive health, which often arise precisely after suffering from the coronavirus disease. A significantly lower success rate of assisted reproductive technologies programs in these patients was established, which is due to the systemic impact of the coronavirus infection on the woman’s body and reproductive function in particular.